Public health practitioners' perspectives of migrant health in an English region. (October 2019) - Staniforth, R.; Such, E.
Abstract: Objectives: Migration is a complex and contested topic of public debate. Professionals working in public health must negotiate this politicised complexity, yet few studies examine the perspectives and practices of public health professionals in relation to migrant health. This study seeks to redress this by exploring how migrant health is conceptualised and addressed by public health professionals after a key transitional point in the reorganisation of public health in England and the public vote for the UK to leave the EU. Study design: This is a qualitative in-depth exploratory study. Methods: Ten interviews and one focus group were conducted with 14 public health professionals working at Public Health England or local authorities in an English region. Recordings were transcribed, and thematic analysis was conducted. Results: Professionals viewed migrant health mainly through a health inequalities lens; migrants were considered vulnerable, and their health was often determined by wider social issues. This influenced public health professionals' perceived ability to affect change. Public health professionals were greatly influenced by the societal, policy and institutional, post-Brexit vote context in England, describing nervousness around addressing migrant health. At an institutional level, public health professionals described a sense that migrant health was not prioritised. It was considered 'too hard' and complex, especially with shrinking resources and highly politicised social narratives. Consequently, migrant health was often not directly addressed in current practice. The gaps identified by public health professionals were as follows: lack of knowledge of health needs and cultural difference; lack of access to appropriate training; lack of cultural diversity within the public health workforce; and concerns about meaningful community engagement. Conclusions: These findings raise concerns about public health professionals' ability to address the health needs of migrants living in England. The gaps highlighted require further and deeper examination across relevant organisations including the broader public health infrastructure in the UK. Highlights: Migrants are viewed as vulnerable; their health is determined by wider social issues. Public health professionals (PHPs) are influenced by the societal, policy and institutional, post-Brexit vote context. Migrant health was not a priority, with fewer resources and a highly politicised narrative. This research raises concerns about PHPs' ability to improve migrant health. Better support structures for PHPs are essential if improvements in migrant health are going to be made.